STUDYING THE CHEMICAL COMPOSITION OF APPLE LEAVE ESSENTIAL OILS (Scientific journal of the Fergana State University, 2025)
The composition of essential oils extracted by hydrodistillation from the dried leaves of two samples of the Semerenko apple variety growing in the Altiaryk district of the Fergana region was studied by gas chromatography-mass spectrometry. According to the results of the study, 39 compounds were identified in the essential oil of the leaves of the Jorak apple and 36 in the essential oil of the leaves of the Poloson apple. The essential oils contain terpene hydrocarbons, monocyclic and bicyclic monoterpenes, sesquiterpenes, phenols, alcohols and derivatives of unsaturated aldehydes and other compounds. The main compounds in the Jorak apple essential oil are R(+)-limonene (12.8%); cis-α-caryophyllene (7.76%); (-)-isoborneol (7.43%); trans-2-hexenal (4.5%); vinylacetonitrile (4.34%); (+)-δ-cadinene (3.94%) and Poloson apple: cyclophenene (21.12%); (-)-isoborneol (11.80%); 1,8-cineole (6.90%); cis-α-caryophyllene (5.84%); 5,9,13-trimethyl-4,8,12-tetradecatrien-1-ol (4.72%); 3,7,11-trimethyl-1-dodecanol (4.65%); trans-2-hexenal (4.48%).